2021
DOI: 10.1038/s41561-020-00677-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced aerosol particle growth sustained by high continental chlorine emission in India

Abstract: 2Cheng, Z. et al. Status and characteristics of ambient PM2.5 pollution in global megacities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(158 citation statements)
references
References 72 publications
11
147
0
Order By: Relevance
“…Production of particle-phase chloride, presumed to be from uptake of gas-phase HCl, has been observed previously during fog/haze events in highly polluted urban India (Gunthe et al, 2021) and near an incinerator (Johnson et al, 1987). However, for this study in Kalamazoo, MI, road salting seems more plausible as the dominant source of increased PM2.5 Clduring wintertime fog.…”
Section: Competing Effects Of Environmental Conditionssupporting
confidence: 55%
“…Production of particle-phase chloride, presumed to be from uptake of gas-phase HCl, has been observed previously during fog/haze events in highly polluted urban India (Gunthe et al, 2021) and near an incinerator (Johnson et al, 1987). However, for this study in Kalamazoo, MI, road salting seems more plausible as the dominant source of increased PM2.5 Clduring wintertime fog.…”
Section: Competing Effects Of Environmental Conditionssupporting
confidence: 55%
“…To further understand the complex urban atmospheric chemistry in Delhi, more model constraints are required, such as the measurement of radical species and k(OH). The potential effects of chlorine chemistry were also not investigated in this study, and may have an important role in the local chemistry due to the prevalence of waste burning in the city (Gunthe et al, 2021). Satellite observations and aircraft measurements may also help develop our understanding of the regional impacts of regional agricultural biomass burning on Delhi from neighbouring states.…”
Section: Discussionmentioning
confidence: 99%
“…However, an ASA reduction will result in a decrease in AOD, which will in turn increase photolysis rates. A recent study by Chen et al, 2021 modelled the impact of AOD on photolysis in Delhi during November 2018, and found that halving the AOD results in a 14 % increase in j(NO2). In Delhi, total VOCs would need to be reduced by ~ 50 % to maintain current P(O3) rates if NOx were halved and photolysis rates increased by 14 %.…”
Section: The Impact Of Aerosol Surface Area On P(o3)mentioning
confidence: 99%
“…Cl − is found in normally coarser particles and its formation might be from the mechanisms i.e., sea salt transformation and photochemical reaction (Chattopadhayay, 2012), biomass burning (Saud et al 2013), and use of fertilizers (Bakeer et al 2016 (Shepherd, 1993). Gunthe et al (2021) Like Cl − spatial variation of Na + is from 1.0 to 56.4 µg m − 3 . The highest concentration of Na + was observed at Rana Pratap Bagh (56.4 µg m − 3 ) (Fig.…”
Section: Water Soluble Ionic Species (Wsis) In Tspmentioning
confidence: 97%